2020
DOI: 10.20527/jcae.v3i1.306
|View full text |Cite
|
Sign up to set email alerts
|

MENINGKATKAN BERPIKIR KREATIF DAN HASIL BELAJAR MENGGUNAKAN MODEL PjBL BERBASIS STEAM PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT

Abstract: Penelitian tentang meningkatkan berpikir kreatif dan hasil belajar peserta didik menggunakan model PjBL berbasis STEAM materi elektrolit dan nonelektrolit di SMAN 7 Banjarmasin bertujuan untuk mengetahui 1) Tindakan yang tepat dalam upaya menangani masalah kelas 2) meningkatkan berpikir kreatif serta hasil belajar. Jenis Penelitian yang diterapkan adalah PTK Model John Elliot dengan tahap rencana, tindakan, pengamatan, dan refleksi, dilakukan di SMAN 7 Banjarmasin di kelas X MIPA 5 dengan objek 38 peserta didi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…These result are in line with previous research (Susanti et al, 2018) which states that there are quite significant differences in competency achievement results (cognitive, affective, and psychomotor) between students who take part in STEAM learning and students who take part in learning using conventional methods. Other research conducted by (Rahman et al, 2020) shows that there is an increase in student learning outcomes after using the PjBL STEAM model in learning. Next, research (Widodo et al, 2021) the results found that there was an increase in the learning outcomes of Class IV students after using STEAM PBL, and from this research, it was also known that STEAM PBL had a significant influence on the learning process.In accordance with the instruments of high-level thinking skills, namely analyzing, evaluating and creating (Ahmad et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…These result are in line with previous research (Susanti et al, 2018) which states that there are quite significant differences in competency achievement results (cognitive, affective, and psychomotor) between students who take part in STEAM learning and students who take part in learning using conventional methods. Other research conducted by (Rahman et al, 2020) shows that there is an increase in student learning outcomes after using the PjBL STEAM model in learning. Next, research (Widodo et al, 2021) the results found that there was an increase in the learning outcomes of Class IV students after using STEAM PBL, and from this research, it was also known that STEAM PBL had a significant influence on the learning process.In accordance with the instruments of high-level thinking skills, namely analyzing, evaluating and creating (Ahmad et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…According to (Žerovnik & Nančovska Šerbec, 2021) said with long-term activities that involve students in designing, making and displaying products to solve real world problems. Thus, the Project Based Learning (PjBL) learning model can be used as a learning model to develop students' abilities in planning, communicating, solving problems and making the right decisions regarding the problems they face (Rahman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%